A BIM-based framework for forecasting and visualizing seismic damage, cost and time to repair - Christodoulou, S. E.; Vamvatsikos, D.; Georgiou, Christodoulos (My University, 2010)
A methodology is presented for integrated and automated forecasting of damage assessment, cost estimating, scheduling and of 3D/4D visualizations for post-earthquake building rehabilitation. The proposed methodology is based on the integration of Building Information Modelling (BIM) and Assembly-Based Vulnerability (ABV) techniques. ABV is a framework for evaluating the seismic vulnerability and performance of structures on a building-specific basis, utilizing seismic analysis techniques to determine the structural response of a building. The methodology used accounts for structural and non-structural building components and corresponding fragility curves, and subsequently applies BIM-based techniques to automate the generation of cost estimates, activity schedules as well as 3D/4D visualizations of the associated rehabilitation work. © 2010 Taylor & Francis Group, London.
Keywords: Flood; Floods; Flood loss